Efficacy of some new insecticides against diamond back moth (Plutella xylostella L.) on cauliflower - S. K. Dotasara; N. Agrawal; Dinesh Swami (Annals of Agricultural Research, 2022)
The efficacy of different insecticides against the diamondback moth (DBM) on cauliflower was studied at CSAUA&T, Kanpur.Among the various insecticides evaluated against the DBM, spinosad (45 SC @ 0.5ml/ litre) treated cauliflower plot showed highest per cent reduction over control (89.97%) with less number of larvae(0.58larvae/plant). The larval count and per cent reduction over control in the different treated plots ranged from 0.58 to 3.94 and 89.97 to 41.37 respectively as against 8.79 numbers of larvae in untreated control. Flubendiamide 48 SC @ 0.3 ml/litre and chlorantriniliprole 18.5 SC @ 0.3 g/litre were next effective pesticides to reduce the pest incidence significantly. All the treatments were also observed to be significantly superior over control.